Path against dengue: Experience report of a university extension project - Brito, Francine Santiago dos Anjos; de Almeida, Larissa Bastos; Mendonça, Ian Paulo; Soares, Roberta Caetano; Ferreira , João Bernardo Santos; Ornelas, Matheus Falcao da Silva; Cardoso , Jéssica Fernanda Avelina e Antunes; Ferraz , Fernanda Almeida; Durante, Pedro Gabriel Gonzaga; Alcântara, Maria Cecília Corrêa; Dias , Túlio Câmara (Seven Editora, 2023)
Dengue is an acute febrile disease with typical viral etiology and benign evolution that is severe when it presents in the hemorrhagic form. Its transmission occurs by the bite of Aedes aegypti, in a human-Aedes aegypti-human cycle. Therefore, care and prevention against dengue is a practice that should always be encouraged, especially in risk areas, in addition to seeking to include the population as participants in prevention actions against this arbovirus. The article is an experience report whose objective is to describe the experience developed and experienced by the students of the undergraduate course in Medicine of UniFipMoc-Afya during the extension project "Path Against Dengue" that took place in May 2022 in the Cândido Canelas Municipal Park, located in the Canelas neighborhood, Montes Claros – MG. The actions carried out had a socio-educational character, aiming to recognize and demarcate the determinants of dengue in the Canelas and Antônio Canelas neighborhoods, in order to sensitize the local community about the preventive measures against the proliferation of the disease and, in this way, contribute to the integralization of the health of the residents. The strategies employed brought reflection, the problematization of the agenda and the valorization of a change in behavior aimed at reducing the transmission of dengue in the Antônio Canelas neighborhood and in Canelas. Therefore, this set of experiences provided the possibility of promoting an advance in the care and prevention of dengue, placing the community itself as a precursor and responsible for the acts that will provide a health promotion and improvements in their lives.DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-124